Public Culture A United States and Asia Comparison: The Role Emotion Display Migrant Labour of Performance Individual (Evidence from Indonesia) - Tari, Erlyna Hidyan (International Journal of Management Excellence (ISSN: 2292-1648), 2019)
This study explores the relationship between emotional immigrant labor and burnout in the context of individualist versus collectivist culture. Based on immigrant labor samples working in the United States and in east and central Asian countries, the results show that: (1) Migrant labor emotions that pretend are positively related to burnout in individualist culture and collectivism. (2) The othentic Migrant labour emotions are negatively related to burnout of individualist culture and collectivism. (3) Emotional pretensions are positively related to individual performance in the culture of collectivism. (4) There is no difference in the relationship between emotional appearance and performance in individualist culture and collectivism. (5) Working for an individualist culture company is more likely to cause burnout than a culture of collectivism. This finding shows the differences in eastern (Asian) and western (American) cultures, but the view of culture is dynamic.